Does Liquidity Shape Dividend Policy? Evidence From Public Firms In An Emerging Market - Sheril Deany Poluan; Ika Prayanthi (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This research aims to re examine the relationship between liquidity and dividend policy by introducing a multidimensional liquidity framework. While traditional studies often rely on single indicators, this study integrates Agency Theory and the Liquidity Hypothesis to explain how distinct liquidity dimensions comprising internal, short term, and structural aspects dictate the Dividend Payout Ratio within an emerging market context. The study employs a quantitative approach with a causal associative design. The sample includes 82 nonfinancial public firms with 272 firm year observations listed on the Indonesia Stock Exchange from 2019 to 2023. Data were analyzed using three separate Random Effect panel regression models to prevent measurement bias and capture the specific impacts of Free Cash Flow for internal liquidity, Current Ratio for short term liquidity, and Cash to Total Assets for structural liquidity on the Dividend Payout Ratio. Results demonstrate that all three liquidity dimensions exert a positive and statistically significant influence on the Dividend Payout Ratio. Specifically, firms with abundant internal cash generation, robust short term solvency, and high structural cash reserves are significantly more inclined to distribute earnings to shareholders. These findings provide strong support for Agency Theory where dividends serve as a disciplining mechanism to mitigate potential management misallocation of excess cash. This research contributes to the literature by addressing the research gap of unidimensional liquidity measurement through a comprehensive multidimensional framework. It offers practical insights for corporate management to balance various liquidity dimensions and provides investors with robust parameters for evaluating the sustainability of dividend distributions in emerging markets.